Post—Ankylotic Temporomandibular Joint Reconstruction Using Autogenous/Alloplastic Materials: Our Protocol and Treatment Outcomes in 22 Patients. Issue 4 (December 2016) - Bhardwaj, Yogesh; Arya, Saurabh
The purpose of this study was to evaluate the various options of autogenous and alloplastic reconstruction modalities available for posttraumatic temporomandibular joint (TMJ) ankylosis. In a retrospective study of 22 patients, various autogenous/alloplastic materials were used based on type and severity of ankylosis and age of patient. Final outcome of reconstruction was critically evaluated in terms of maximal mouth opening, occlusion, and facial symmetry. Fourteen patients (63.63%) developed TMJ ankylosis due to road traffic accidents and eight patients (36.36%) had a history of fall. The mean age was 15.61 years. The mean preoperative maximum interincisal mouth opening (MIMO) for the entire series was 3.39 mm ± 2.16 and postoperative MIMO was 43.69 mm ± 2.63. Costochondral grafts were used in seven children, whereas titanium reconstruction plate with condylar head was used in five adults and interpositional arthroplasties using temporalis muscle, temporalis fascia, and relocation of the articular disc were used in the rest of the ten patients. We conclude that all these age-specific treatment modalities yield clinically comparable results in terms of postoperative mouth opening and facial symmetry with no evidence of reankylosis in a follow-up ranging from 24 to 96 months.